ASTRAGALOSIDE IV LIPOSOMES AMELIORATES ADRIAMYCIN-INDUCED NEPHRITIC SYNDROME IN RATS MING-GANG - Wei, Ming-gang; He, Wei-ming; Zhang, Ling; Yan, Zhao-wei; Yang, Yan-Yu; Xiong, Pei-Hua; Sun, Wei (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Radix Astragali was one of the main composition of ‘Modified Danggui Buxue Decoction’ used for treatment of various kidney diseases. Astragaloside IV was the active composition of Radix Astragali. Astragaloside IV liposomes were used for the treatment of adriamycin-induced nephropathy (AN) rats. The aim of the study was to study the effect of astragaloside IV liposomes on AN rats, and to test through regulating the expression of nephrin, integrins and integrin-linked kinase (ILK) in renal tissues. Methods: The rats were given a single tail intravenous injection of adriamycin (6 mg/kg) within 1 weeks, and then divided into four groups including normal, model, benazepril and astragaloside IV liposomes group. They were all orally administered dosage of benazepril and astragaloside IV liposomes once daily for 8 weeks. Results: Astragaloside IV liposomes significantly reduced the proteinuria of AN rats at 28, 42 and 56 days. astragaloside IV liposomes could increase the mRNA and protein expression of nephrin, integrin α3, down-regulate the expression of ILK to alleviate the podocyte damage and restore glomerular selective filtration function. Conclusions: Astragaloside IV liposomes could enhance renal function and protect podocyte to ameliorate the adriamycin-induced nephritic syndrome.